Cytomegalovirus infections in lung and hematopoietic cell transplant recipients in the Organ Transplant Infection Prevention and Detection Study: A multi‐year, multicenter prospective cohort study. Issue 3 (30th March 2018) - Avery, Robin K.; Silveira, Fernanda P.; Benedict, Kaitlin; Cleveland, Angela A.; Kauffman, Carol A.; Schuster, Mindy G.; Dubberke, Erik R.; Husain, Shahid; Paterson, David L.; Chiller, Tom; Pappas, Peter
Abstract: Background: Most studies of post‐transplant CMV infection have focused on either solid organ or hematopoietic cell transplant (HCT) recipients. A large prospective cohort study involving both lung and HCT recipients provided an opportunity to compare the epidemiology and outcomes of CMV infections in these 2 groups. Methods: Patients were followed up for 30 months in a 6‐center prospective cohort study. Data on demographics, CMV infections, tissue‐invasive disease, recurrences, rejection, and immunosuppression were recorded. Results: The overall incidence of CMV infection was 83/293 (28.3%) in the lung transplant group and 154/444 (34.7%) in the HCT group ( P  = .0706). Tissue‐invasive CMV disease occurred in 8/83 (9.6%) of lung and 6/154 (3.9%) of HCT recipients with CMV infection, respectively ( P  = .087). Median time to CMV infection was longer in the lung transplant group (236 vs 40 days, P  < .0001), likely reflecting the effects of prophylaxis vs preemptive therapy. Total IgG levels of < 350 mg/dL in lung recipients and graft vs host disease (GvHD) in HCT recipients were associated with increased CMV risk. HCT recipients had a higher mean number of CMV episodes ( P  = .008), although duration of viremia was not significantly different between the 2 groups. CMV infection was not associated with reduced overall survival in either group. Conclusions: Current CMV prevention strategies have resulted in a low incidence of tissue‐invasive disease in both lung transplant and HCT, although CMV viremia is still relatively common. Differences between the lung and HCT groups in terms of time to CMV and recurrences of CMV viremia likely reflect differences in underlying host immunobiology and in CMV prevention strategies in the modern era.